The Youth First Computer Centre [Solomon Islands] - Tutuo, Hemaima (Technical Centre for Agricultural and Rural Cooperation, 2004)
Hemaima Tutuo reports on the first few months and future plans of a recently established ICT learning centre in the Solomon Islands